Isolated Pancreatic Metastasis of a Malignant Pleural Mesothelioma - Yi-Ting Lin; Bing-Shiun Wu; Sheau-Fang Yang; Huang-Chi Chen (Kaohsiung Journal of Medical Sciences, 2009)
Metastatic malignant mesothelioma of the pleura is uncommon at the time of initial diagnosis. When metastases are present, the major sites always include regional lymph nodes, the contralateral lung, liver, adrenal glands and kidneys. Here, we describe an extremely rare case of isolated pancreatic metastasis of mesothelioma of the pleura in a 40-year-old man who initially presented with epigastric discomfort and hunger pain, which were refractory to medical treatments. The possibility of pancreatic metastatic lesion should be considered in patients with malignant pleural mesothelioma in the presence of refractory epigastric tenderness.